Perceived susceptibility to developing cancer and mammography screening behaviour: a cross-sectional analysis of Alberta's Tomorrow Project. (December 2019) - Gilfoyle, M.; Garcia, J.; Chaurasia, A.; Oremus, M.
Abstract: Objectives: Cross-sectional data from Alberta's Tomorrow Project (ATP) were used to assess the association between perceived susceptibility (PS) to developing cancer and mammography screening behaviour. Study design: Cross-sectional study. Methods: ATP participants between 35 and 70 years of age who reported being free of chronic conditions were included in the study (n = 1803). PS was measured using three variables: participants' estimate of their personal PS of developing cancer, compared to others, on a 5-point Likert scale; participants' estimate of the percentage of people in their age group who would be diagnosed with cancer; and participants' estimate of their own chance (expressed as a percentage) of being diagnosed with cancer. Multivariable logistic regression models, adjusting for age, marital status, work status, education, family history, and place of residence, were used to explore the association of interest. Results: PS of developing cancer was modestly yet significantly associated with mammography screening behaviour for two of the three PS variables. Specifically, the adjusted odds of mammography screening were 1.20 times greater for each one-unit increase in personal PS of developing cancer (95% confidence interval [CI] = 1.07–1.36 [ P  = 0.003]) and 1.01 times greater for each one-unit increase in both participants' estimate of the percentage of people who would develop cancer (95% CI = 1.00–1.01 [ P  = 0.05]) and participants' estimate of their own chance of developing cancer (95% CI = 1.00–1.01 [ P  = 0.02]). Conclusions: Understanding how certain factors, such as PS, are associated with screening behaviour is important to help address the underutilization of cancer screening. Highlights: Perceived susceptibility to cancer may be associated with screening. Higher perceived risk/chance of cancer was associated with mammography screening. A focus on individual perceived susceptibility may be a tool to increase screening.